A new narration of the concept “identity” and method for teaching identification - Davarpanah, Aboo Sa’eed; Khanjarkhani, Masoud (Opción, 2019)
The main objective of the current paper is offering a new narration of the concept “identity” as well as a method of teaching identification based on Hans-Georg Gadamer‟s philosophical hermeneutics. The “formation of identity” is a process happening in the grounding of constant speculative interaction. In the end, identity is a product that begins with self-understanding, is adjusted by other-understanding and leads to co-understanding and the absence of speculative interactions and a constant challenging force are taken as crises.